Tunnel and Microtunnel For Future Smart and Sustainable Infrastructure Solution - Siti Norafida Jusoh; Abdullah Rini Asnida; Marto Aminaton; Fauziah Kassim (IPTEK Journal of Proceedings Series, 2017)
Underground facilities and tunnels is not a rare discussion anymore. More and more underground explorations were carried out as to fulfil the need of mankind. In this paper, discussion on how to utilise tunnel and underground space knowledge in order to sustain green development thus to provide smart solution for infrastructure facilities (electrical cable, manhole etc) is discussed. Types of tunnel and its excavation methods especially the recent micro-tunnelling method also presented. Affect to the green and sustainable development and case study are also presented.